2015
DOI: 10.1530/eje-15-0277
|View full text |Cite
|
Sign up to set email alerts
|

Is surgery necessary for ‘mild’ or ‘asymptomatic’ hyperparathyroidism?

Abstract: A large majority of the currently diagnosed patients with hyperparathyroidism (PHPT) are mild or asymptomatic, mainly women after menopause. Following the debate held at the 16th European Congress of Endocrinology in Wroclaw (Poland) from May 3-7, 2014, arguments are here presented by a surgeon and a medical practitioner considering these situations rather have to profit from surgery, or simply from survey. For the trained endocrine surgeon, it is evident that parathyroidectomy confirms the diagnosis and undou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Delayed recognition scores trended toward improvement. A comparison of these results (Table ) to the following age‐controlled normative data—ages 50 to 59 years, immediate recall 6.2 (standard deviation [SD] 1.2), delayed recall 9.9 (SD 3.2), and delayed recognition 13.9 (SD 1.4)— reveals that patients in the study had lower than normal immediate memory, delayed recall, and delayed recognition prior to surgery, which improved to above average after surgery.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Delayed recognition scores trended toward improvement. A comparison of these results (Table ) to the following age‐controlled normative data—ages 50 to 59 years, immediate recall 6.2 (standard deviation [SD] 1.2), delayed recall 9.9 (SD 3.2), and delayed recognition 13.9 (SD 1.4)— reveals that patients in the study had lower than normal immediate memory, delayed recall, and delayed recognition prior to surgery, which improved to above average after surgery.…”
Section: Resultsmentioning
confidence: 88%
“…However, in the years since serum calcium levels became part of routine laboratory testing, increasing the numbers of patients are being diagnosed incidentally who are presumably asymptomatic. In these cases, the indications for surgical management are not universally agreed upon …”
Section: Introductionmentioning
confidence: 99%
“…A particular problem occurs in asymptomatic cases. A series of long‐term prospective studies have shown that mild and asymptomatic PHPT is usually stable and sometimes very slightly progressive . Many clinicians would avoid surgery for mild and asymptomatic PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…In the current guidelines [1], “asymptomatic” patients compose a patients’ group inheriting only a “relative indication” for surgery while in “symptomatic” patients early surgical intervention is recommended [23], so those patient groups need to be discriminated [24]. …”
Section: Discussionmentioning
confidence: 99%